Tantangan Guru dalam Menyusun dan Menerapkan Modul Ajar MIN 3 Lhokseumawe - Faiza Nazira; Julrissani Julrissani; Atika Salsabila; Majelita Hasibuan; Maulina Fitri (PT Cendekia Education Center, 2026)
This study aims to describe the challenges faced by teachers in developing and implementing teaching modules under the Merdeka Curriculum at MIN 3 Lhokseumawe. This study employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation, and were analyzed using an interactive analysis model. The findings revealed that teachers encountered several challenges in developing teaching modules, including differences in understanding the format and components of teaching modules, limited practical training, and time constraints due to teaching and administrative responsibilities. In implementing the teaching modules, teachers also faced challenges related to discrepancies between lesson plans and classroom practices, the need to adjust instruction to classroom conditions, and teacher readiness in responding to dynamic learning situations. To address these challenges, the school conducted academic supervision, evaluated teaching documents, organized teacher discussions and mentoring activities, and encouraged participation in the MOOC Pintar training program provided by the Ministry of Religious Affairs. The findings are expected to provide input for improving the quality of teaching module development and implementation in madrasahs.